Performance evaluation of bluetooth low energy for high data rate body area networks - Afonso, José A. (2016)
Bluetooth Low Energy (BLE) is a promising wireless network technology, in the context of body area network (BAN) applications, to provide the required quality of service (QoS) support concerning the communication between sensor nodes placed on a user’s body and a personal device, such as a smartphone. Most previous BLE performance studies in the literature have focused primarily in networks with a single slave (point-to-point link) or traffic scenarios with relatively low data rate. However, many BAN sensors generate high data rate traffic, and several sensor nodes (slaves) may be actively sending data in the same BAN. Therefore, this work focuses on the evaluation of the suitability of BLE mainly under these conditions. Results show that, for the same traffic, the BLE protocol presents lower energy consumption and supports more sensor nodes than an alternative IEEE 802.15.4-based protocol. This study also identifies and characterizes some implementation constraints on the tested platforms that impose limits on the achievable performance.